2020
DOI: 10.1090/conm/744/14983
|View full text |Cite
|
Sign up to set email alerts
|

Equicontinuity of minimal sets for amenable group actions on dendrites

Abstract: In this note, we show that if G is an amenable group acting on a dendrite X, then the restriction of G to any minimal set K is equicontinuous, and K is either finite or homeomorphic to the Cantor set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In Section 6 we show that for an amenable group G every infinite minimal set in a dendrite system (G, X) is almost automorphic. This result was strengthened recently by Shi and Ye [40], who have shown that it is actually equicontinuous. In the final section we comment on the special case where the acting group is the group of integers.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In Section 6 we show that for an amenable group G every infinite minimal set in a dendrite system (G, X) is almost automorphic. This result was strengthened recently by Shi and Ye [40], who have shown that it is actually equicontinuous. In the final section we comment on the special case where the acting group is the group of integers.…”
Section: Introductionmentioning
confidence: 71%
“…On 4 July, 2018, Shi and Ye provided a negative answer [40]: Theorem 6.6. Let G be an amenable group acting on a dendrite X.…”
Section: Tame Actions Of Amenable Groups On Dendritesmentioning
confidence: 99%
“…However, the exact analogy to the rigidity results by Witte-Morris and Deroin-Hurtado mentioned above do not hold anymore for higher rank group actions on dendrites; in fact, it is easy to see that every countable infinite group can act faithfully on a starlike dendrite of infinite order; even if the dendrite X we considered is assumed to be of finite order, there can still exist a faithful higher rank lattice action on it (see Section 6 for examples). One may consult [1,5,9,15] for some related discussions around dendrite homeomorphism groups.…”
Section: Introductionmentioning
confidence: 99%
“…Some people studied the Ghys-Margulis' alternative for dendrite homeomorphism groups ( [18,15,8]). One may consult [1,12,20] for the discussions around the structures of minimal sets for group actions on dendrites. The algebraic structures of dendrite homeomorphism groups were investigated in [7] Duchesne-Monod proved the existence of finite orbits for higher rank lattice actions on dendrites ( [8]).…”
Section: Introductionmentioning
confidence: 99%